MLTI-08. AN EXCEPTIONAL INTRACRANIAL RESPONSE TO REPEAT RADIATION AND IMMUNOTHERAPY IN A PATIENT WITH METASTATIC, POORLY DIFFERENTIATED ADENOCARCINOMA OF THE LUNG. (12th August 2019) - Sumrall, Ashley; Burri, Stuart; Asher, Anthony
Abstract: We report an unusual case of a long-term survivor of metastatic, poorly differentiated adenocarcinoma of the lung (EGFR- ALK-) who developed intracranial disease after definitive treatment of a stage IIIB lung cancer. He received a complex course of RT which began with SRS to his intracranial disease in 2012 and included: brainstem (pontine) mass, left parietal mass, left frontal, left lateral temporal, and left insular lesions. The left temporal mass progressed and was resected. Subsequently, SRS was given to a right anterior frontal lesion. Additional SRS was given to progressive right superior frontal mass & left temporal tumor bed was given fractionated RT to the left temporal tumor bed. Later, he developed bilateral cerebellar masses and right-sided progression. More SRS was given to right frontal area, and then to bilateral cerebellar lesions. Surprisingly, he did well neurologically until seizures developed. His repeat biopsy was sent for NGS and noted to be PDL1+, APC mutated, and KRAS mutated. This gentleman was started on pembrolizumab in May 2016. Due to colitis, his therapy stopped in January 2017. His colitis progressed such that immunotherapy could not be restarted. Now, after observation only for the past 2.5 years. his disease has disappeared. He is doing well neurologically. We propose that the use of radiation and immunotherapy worked to produce an exceptional, durable response.